The opportunities afforded by offshore teaching to faculty members: Strengthening confidence in core qualities. Issue 2 (4th March 2023) - Saito, Eisuke; Ab Kadir, Mohammad Akshir; Grove, Christine
ABSTRACT: Offshore teaching is a common practice in Australian higher education. While challenges in offshore teaching have been well studied, the opportunities that it may provide have been seldom discussed. Considering this, the aim of this study is to address this gap by investigating the opportunities that offshore teaching provided faculty members in the development of their professional values. This study employs the memory-work method self-study based on the reflective notes of Author1 about his teaching experiences in the offshore programme between December 2019 and August 2021, with reference to Korthagen's core reflection model. The reflections revealed that he not only identified but strengthened his confidence in his core qualities through offshore teaching. This strengthened confidence in his core qualities also helped him to negotiate with the new problematic situations created by the COVID-19 pandemic.